Radon Surface Exhalation Rates in Sediment Samples of Mekong River and Lung Cancer Risk, Nakhon Phanom Province, Thailand - Pookamnerd, Yodprem; Thopan, Prutchayawoot; Temprom, Likit; Poochada, Worawan; Atyotha, Vitsanusat (YRU Journal of Science and Technology, 2023)
Radon, a radioactive gas, is produced through the decay of uranium present in the soil. The levels of radon can fluctuate. As radon undergoes decay, it emits α-particles and undergoes exhalation, leading to the release of the gas from the ground into the air. Inhalation of radon increases cancer risk by damaging DNA through α-particle interactions. To better understand this, an investigative study collected 50 sediment samples at a depth of 20 cm from various districts in Nakhon Phanom province, Thailand (including Ban Phaeng, Tha Uthen, and Mueang districts). Radon concentrations were measured using an active detecting method (RAD 7). The results revealed that radon concentrations ranged from 2.75 to 73.50 Bq/m3, with an average value of 27.69±1.94 Bq/m3. It is noteworthy that all measured radon concentrations were notably lower than the maximum allowable contamination level of 100 Bq/m3, which is recommended by the WHO. Radon surface exhalation rates varied between 1.83 and 48.78 mBq/m2/h, with an average of 18.38±1.29 mBq/m2/h. Notably, the radon surface exhalation rate observed in these studies was lower than the global average value of 57,600 mBq/m2/h, as recommended by UNSCEAR. These findings were crucial in assessing the associated health risks, highlighting significant hazards for individuals. The average annual effective dose (AED) remained below the WHO threshold of 100 µSv/y, and the average number of lung cancer cases per million people (LCC) was calculated as 12.57×10-6. Consequently, these findings indicate that 12.57 out of 1,000,000 people in the research area face a risk of developing lung cancer due to radon exposure in the Mekong River sediments.